(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
When operating a vehicle for the transportation of agricultural goods, the final planning decision should be selected by the technical and economic calculation according to the size of the total reduced costs. Inthiscase, it is necessary to take into account the cost of transportation, maintenance costs, operating and motor costs for each option, losses from the economy fromroadtrafficaccidents.